Stigmas arrangement, reproductive system, and maternal reproductive success in two species of Stigmaphyllon (Malpighiaceae): does pollinator size matter? - Avalos, Adan Alberto (2021)
Most species of Neotropical Malpighiaceae are pollinated by oil-collecting bees of diverse sizes, but the effect of pollinator size on their reproductive success has still not been addressed in the literature. We performed a comparative description of stigma arrangements, analyzing the reproductive system and reproductive success and assessing pollinator sizes in Stigmaphyllon bonariense and Stigmaphyllon jatrophifolium. We collected flowers in three natural populations, conducting pollinator censuses and captures and performing manipulative experiments to determine the plants breeding system. We analyzed the morphology of stigmas and their receptivity and calculated the perimeter of the triangle formed by the stigmas (ST). Pollinator sizes, potential area for pollen transfer (PAPT), and the frequency of visits were also calculated. Stigma arrangement resulted in inverted triangles, and the ST was smaller in S. jatrophifolium than in S. bonariense. The overlap between ST and PAPT suggests that pollinators of all sizes were efficient in pollinating S. jatrophifolium, whereas only large and very large pollinators where efficient in S. bonariense. Moreover, very large pollinators had the highest visit frequencies. Our results indicated that both species are obligate xenogamous, pollinator-dependent, and present pollen limitation. We observed an increase in reproductive success related to the marked turnover in pollinator assemblage throughout the flowering season. These findings suggest that fruit and seed sets vary according to the context of the pollinators and that large pollinators would have the best performance.